A study on the factors that influence the transfer of training among KWSP staff / Nazhatul Azwa Ali and Fatimatul Saadiah Abd Rashid - Ali, Nazhatul Azwa; Abd Rashid, Fatimatul Saadiah (Faculty of Business and Management, 2014)
Purpose of this study is to identify the factors that influence of training among KWSP staff in Melaka and Temerloh. The researchers have chosen KWSP to represent this study. Researchers have listed two variables which are trainee’s motivations and training design as the independent variables and transfer or training as dependent variables. Researchers have distributed 52 sets of questionnaires to our target respondent which is to staff in Operation Department and Services only. 25 respondents come from KWSP of Temerloh and the rest came from KWSP of Melaka. This study discussed the factors that influence the transfer of training among staff in KWSP. The findings and analysis were made based on Statistical Package for social science (SPSS) version 21.0 to analyse the data. The findings of this study prove that trainee’s motivation, training design positively affect the transfer of training to all staff in KWSP